Co-Inoculation of Soybean Seeds with Azospirillum and/or Rhizophagus Mitigates the Deleterious Effects of Waterlogging in Plants under Enhanced CO2 Concentrations - Eduardo Pereira Shimoia; Douglas Antônio Posso; Cristiane Jovelina da-Silva; Adriano Udich Bester; Nathalia Dalla Corte Bernardi; Ivan Ricardo Carvalho; Ana Cláudia Barneche de Oliveira; Luis Antonio de Avila; Luciano do Amarante (Nitrogen)
Rising CO2 levels, as predicted by global climate models, are altering environmental factors such as the water cycle, leading to soil waterlogging and reduced oxygen availability for plant roots. These conditions result in decreased energy production, increased fermentative metabolism, impaired nutrient uptake, reduced nitrogen fixation, and altered leaf gas exchanges, ultimately reducing crop productivity. Co-inoculation techniques involving multiple plant growth-promoting bacteria or arbuscular mycorrhizal fungi have shown promise in enhancing plant resilience to stress by improving nutrient uptake, biomass production, and nitrogen fixation. This study aimed to investigate carbon and nitrogen metabolism adaptations in soybean plants co-inoculated with Bradyrhizobium elkanii, Azospirillum brasilense, and Rhizophagus intraradices under waterlogged conditions in CO2-enriched environments. Plants were grown in pots in open-top chambers at ambient CO2 concentration (a[CO2]) and elevated CO2 concentration (e[CO2]). After reaching the V5 growth stage, the plants were subjected to waterlogging for seven days, followed by a four-day reoxygenation period. The results showed that plants’ co-inoculation under e[CO2] mitigated the adverse effects of waterlogging. Notably, plants inoculated solely with B. elkanii under e[CO2] displayed results similar to co-inoculated plants under a[CO2], suggesting that co-inoculation effectively mitigates the waterlogging stress, with plant physiological traits comparable to those observed under elevated CO2 conditions.